2020
DOI: 10.1073/pnas.2000529117
|View full text |Cite
|
Sign up to set email alerts
|

Untangling the sequence of events during the S 2 → S 3 transition in photosystem II and implications for the water oxidation mechanism

Abstract: In oxygenic photosynthesis, light-driven oxidation of water to molecular oxygen is carried out by the oxygen-evolving complex (OEC) in photosystem II (PS II). Recently, we reported the room-temperature structures of PS II in the four (semi)stable S-states, S1, S2, S3, and S0, showing that a water molecule is inserted during the S2→ S3transition, as a new bridging O(H)-ligand between Mn1 and Ca. To understand the sequence of events leading to the formation of this last stable intermediate state before O2formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
354
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(396 citation statements)
references
References 78 publications
22
354
6
Order By: Relevance
“…Both Mn1 and Mn4 are discussed as possible sites of water binding in the S 2 →S 3 transition because they can offer a coordination site in the S 2 state. Observations relating to methanol and ammonia interaction with the OEC in the S 2 state support the idea that water binds externally to a 5‐coordinated Mn4 site, [30, 36] whereas other alternatives include the shift of a Ca‐bound or a second‐sphere water molecule embedded in the surrounding hydrogen‐bonded water network to either of the terminal Mn ions [37–39] . Pulse ENDOR studies on spinach PSII using 13 C‐ or 2 H‐ labeled methanol are consistent with MeOH positioned either close to Mn4 or close to Ca 2+ in the S 2 state [9] and hence water delivery might be arrested by MeOH from either direction.…”
Section: Resultsmentioning
confidence: 75%
“…Both Mn1 and Mn4 are discussed as possible sites of water binding in the S 2 →S 3 transition because they can offer a coordination site in the S 2 state. Observations relating to methanol and ammonia interaction with the OEC in the S 2 state support the idea that water binds externally to a 5‐coordinated Mn4 site, [30, 36] whereas other alternatives include the shift of a Ca‐bound or a second‐sphere water molecule embedded in the surrounding hydrogen‐bonded water network to either of the terminal Mn ions [37–39] . Pulse ENDOR studies on spinach PSII using 13 C‐ or 2 H‐ labeled methanol are consistent with MeOH positioned either close to Mn4 or close to Ca 2+ in the S 2 state [9] and hence water delivery might be arrested by MeOH from either direction.…”
Section: Resultsmentioning
confidence: 75%
“…Calcium is a critical cofactor in the process of H 2 O oxidation by PSII because it mediates the delivery of substrate water to a Mn coordination site for oxidation and dioxygen formation (20). While an early study suggested that Ca 2+ is not required for photoassembly of the Mn cluster (21), this was later reevaluated (22), and there is now general agreement that Ca 2+ is vital (11,13,22).…”
Section: Significancementioning
confidence: 99%
“…It has been shown by experiments that only an electron leaves in the transition, 32 while the proton leaves in the next transition. 9 , 10 , 33 42 For the W1(H 2 O) + model, the electron released comes from Mn4, while for the W1(OH) model it comes from Mn2. In S 2 , the oxidation states are thus the same for both models with only Mn1 being Mn(III).…”
Section: Resultsmentioning
confidence: 99%
“… 3 , 4 However, the structures of the four observable intermediates in the process, S 0 to S 3 , have now been determined to high precision. 5 10 The most recent experimental determinations of the structures have been done using the X-ray free electron laser (X-FEL) technique. The structure of the oxygen-evolving complex (OEC) has long been known to contain four manganese atoms and a calcium held together by bridging oxo groups.…”
Section: Introductionmentioning
confidence: 99%